1. x^{3/2}($\displaystyle \sqrt{x}$ - 1/ $\displaystyle \sqrt{x}x^{2}$)
Made a attempt
x^{3/4} - x^{ 3/4}/x
= x^{3/2}. x^{1/2} - x^{3/2}/ (x^{1/2}. x^{3/2})
= x^{2}-x^{3/2}/x^{2}
= 1-x^{1/2}
1. x^{3/2}($\displaystyle \sqrt{x}$ - 1/ $\displaystyle \sqrt{x}x^{2}$)
Made a attempt
x^{3/4} - x^{ 3/4}/x
= x^{3/2}. x^{1/2} - x^{3/2}/ (x^{1/2}. x^{3/2})
= x^{2}-x^{3/2}/x^{2}
= 1-x^{1/2}
I think you're multiplying exponents when you should be adding. Try again, using these properties of exponents:
$\displaystyle a^ma^n = a^{m+n}$
$\displaystyle \frac{a^m}{a^n} = a^{m-n}$
$\displaystyle a^{-n} = \frac1{a^n}$
$\displaystyle a^{m/n} = \sqrt[n]{a^m}$
So, for example, $\displaystyle x^{3/2}\cdot x^{1/2}=x^2$.